The Roles of PPARs in the Fetal Origins of Metabolic Health and Disease - William D. Rees; Christopher J. McNeil; Christopher A. Maloney (PPAR Research)
Beyond the short-term effects on fertility, there is increasing evidence that obesity or the consumption of an inappropriate diet by the mother during pregnancy adversely affects the long-term health of her offspring. PPAR and RXR isotypes are widely expressed in reproductive tissues and in the developing fetus. Through their interactions with fatty acids, they may mediate adaptive responses to the changes in the maternal diet. In the maturing follicle, PPAR-γ has an important role in the granulosa cells that surround the maturing oocyte. After fertilisation, PPAR-γ and PPAR-β/δ are essential regulators of placentation and the subsequent development of key metabolic tissues such as skeletal muscle and adipose cells. Activation of PPAR-γ and PPAR-β/δ during fetal development has the potential to modify the growth and development of these tissues. PPAR-α is expressed at low levels in the fetal liver, however, this expression may be important, as changes in the methylation of DNA in its promoter region are reported to take place during this period of development. This epigenetic modification then programmes subsequent expression. These findings suggest that two separate PPAR-dependent mechanisms may be involved in the fetal adaptations to the maternal diet, one, mediated by PPAR-γ and PPAR-β/δ, regulating cell growth and differentiation; and another adapting long-term lipid metabolism via epigenetic changes in PPAR-α to optimise postnatal survival.